2022
DOI: 10.3389/fpsyg.2022.976471
|View full text |Cite
|
Sign up to set email alerts
|

Practice of sustainable fashion design considering customer emotions and personal tastes

Abstract: This study aimed to determine a sustainable design practice approach that can satisfy customer emotions and personal tastes, which designers need in the early stages of the SFD process, and improve environmental performance. The research was conducted through a case study and interviews. For case studies, the specific design methods of fashion brands, which have been ranked sustainable over the last 3 years in the world’s top fashion magazines favored by the public, were researched. The results of the case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The need to reduce the negative impacts of the fashion industry has spurred sustainability initiatives aimed at decreasing carbon footprint, minimizing water pollution, and promoting the use of renewable or recyclable materials. 31 The implementation of sustainable practices in the fashion industry also has a profound impact on brand reputation and integrity while fostering innovation and healthy competition within the industry. This aligns with the findings of a study by Park & Kim, which revealed that fashion brands voluntarily embracing sustainability as a vital part of their concept development receive a more favorable response from consumers compared to those who adopt sustainability due to market pressure, government regulations, consumer demands, or societal expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The need to reduce the negative impacts of the fashion industry has spurred sustainability initiatives aimed at decreasing carbon footprint, minimizing water pollution, and promoting the use of renewable or recyclable materials. 31 The implementation of sustainable practices in the fashion industry also has a profound impact on brand reputation and integrity while fostering innovation and healthy competition within the industry. This aligns with the findings of a study by Park & Kim, which revealed that fashion brands voluntarily embracing sustainability as a vital part of their concept development receive a more favorable response from consumers compared to those who adopt sustainability due to market pressure, government regulations, consumer demands, or societal expectations.…”
Section: Discussionmentioning
confidence: 99%
“…It is a design thinking in which a dress can be altered into multiple shapes using various manipulation techniques, such as binding, wrapping, tumbling, bending, attaching, folding, and assembling. With the use of multi-functional design, a piece of clothing may be worn in a variety of ways to suit various demands and objectives, including behavioral, functional, and decorative ones [20]. In order to minimize entire apparel usage, multi-functional fashion design may be used to shift out, rearrange, or replace clothing pieces.…”
Section: Multi-functional Design Thinking and Practicementioning
confidence: 99%